Introducing plea bargaining in Ethiopia : concerns and prospects - Meheretu, Alemu (2014)
The thesis is about a contextual and prospective analysis of the Ethiopian variant of plea bargaining focusing on the major components of legal culture, legal structure and principles of criminal law and procedure. To this end, it makes use of a thorough analysis of policy and reform documents, laws, as well as comparative literature, interviews and questionnaires. The thesis argues that the Ethiopian variant of plea bargaining is less desirable and feasible. It hardly fits into the Ethiopian legal system for it is constrained by inherent due process concerns in an exacerbated fashion as well as structural/institutional and cultural limitations. Here three subarguments emerge: First, plea bargaining which inherently relates less to evidence and circumvents fundamental principles of criminal law and procedure, aimed at ensuring the integrity of the process, is likely to yield , inter alia, inaccurate outcomes- the innocence problem. With a less developed legal structure (weak defence in particular) and weak legal culture/rule of law, the problem would be exceptionally formidable in Ethiopia. Second, huge structural and functional limitations of legal institutions- the police, the prosecution, the judiciary, and the defence/legal aid, mean plea bargaining would not fare well. Third, plea bargaining tends to be incompatible with the prevailing legal culture. In America and Western Europe, it is often characterized by problems of fairness and outcome inaccuracy. On the face of weak legal culture/rule of law, it remains to be more so in Ethiopia. While plea bargaining may solve problems of delay and enhance efficiency in many jurisdictions, it is not a universal prescription, though. With jurisdictions like Ethiopia whose legal institutions and legal culture are less developed; whose trial appears to be simple, inexpensive, less utilized and correlates very loosely as an underlying cause of delay, plea bargaining is less likely to offer the desired efficiency gains even at all costs. Conversely, it would be more of a liability than an asset at least in three senses: it is likely to yield inaccurate outcomes- wrongful convictions in an aggravated fashion; put defendant`s rights at greater risk, and leave a room for abuses and corruptions.